Productive Zakat as Economic Empowerment Mustahiq Amil Zakat Institute Daarut Tauhid Peduli Lampung - Mustofa, Ulul Azmi; Novita, Resilia (Az-Zarqa': Jurnal Hukum Bisnis Islam, 2022)
Abstract: Poverty is not just an individual or personal problem, but poverty is a common problem. The Amil Zakat Institute Daarut Tauhid Cares Lampung with the productive zakat program must be able to answer these problems. This study aims to determine the mechanism and pattern of productive zakat empowerment applied by LAZ Daarut Tauhid Peduli Lampung and want to know its impact on mustahik. This type of research is a field research conducted at LAZ Daarut Tauhid Peduli Lampung. The results of this study are the mechanisms and patterns used for empowerment in LAZ Daarut Tauhid Lampung are using the Economic Care program (Misykat program, Independent Cattle Village, and Independent Farming Business), this program focuses on capital loans in helping Mustahik's economic empowerment. The Economic Care Program is beneficial for the economic empowerment of Mustahik (increasing income, knowledge, independence and independence).Abstrak: Kemiskinan bukan hanya permasalahan individu atau personal, tetapi kemiskinan merupakan permasalahan bersama. Lembaga Amil Zakat Daarut Tauhid Peduli Lampung dengan adanya program zakat produktif harus mampu untuk memjawab permasalahan tersebut. Penelitian ini bertujuan untuk mengetahui mekanisme dan pola pemberdayaan zakat produktif yang duterapkan oleh LAZ (Lembaga Amil Zakat) Daarut Tauhid Peduli Lampung dan ingin mengetahui dampaknya terhadap mustahik. Jenis penelitian ini adalah penelitian lapangan yang dilakukan di LAZ (Lembaga Amil Zakat) Daarut Tauhid Peduli Lampung. Hasil dari penelitian ini adalah mekanisme dan pola yang digunakan untuk pemberdayaan di LAZ (Lembaga Amil Zakat) Daarut Tauhid Lampung adalah menggunakan program Peduli Ekonomi (program Misykat, Desa Ternak Mandiri, dan Usaha Tani Mandiri), program ini terfokus pada pinjaman modal dalam membantu pemberdayaan ekonomi Mustahik. Program Peduli Ekonomi bermanfaat bagi pemberdayaan ekonomi para Mustahik (peningkatan pendapatan, pengetahuan, kemandirian dan kemndirian).